Digitalization and Strategic Development in Enhancing Islamic Pawnshop Products for Financial Inclusion - Haliding, Safri; Alfiani, Alfiani; Majid, Jamaluddin; Badollahi, Ismail; Marsuni, Nur Sandi (Invoice : Jurnal Ilmu Akuntansi, 2025)
The advancement of Islamic pawnshops in the digital era reflects a strategic move toward increasing competitiveness and enhancing financial inclusion. This study aims to examine the implementation and effectiveness of the Digital Islamic Pawnshop Information System, particularly in improving service accessibility, operational efficiency, and customer engagement. Using a qualitative approach with case analysis and literature synthesis, the study identifies key benefits such as remote transaction capabilities, streamlined application processes, and improved customer responsiveness. Findings indicate that digital transformation in Islamic pawnshops significantly contributes to financial inclusion by expanding access for underserved communities. However, the transition also faces challenges, including limited internet infrastructure, digital literacy gaps, and cybersecurity risks. To address these issues, Islamic pawnshops have adopted digital education initiatives and are gradually strengthening data protection protocols. This study highlights the need for continuous innovation and policy support to optimize digital service delivery in Islamic finance, reinforcing its role in achieving inclusive economic development.